PENGARUH RASIO KEUANGAN TERHADAP PERTUMBUHAN LABA - Tien Kartika Kumala Dewi; Yuli Chomsatu Samrotun (IAIN Lhokseumawe, 2021)
This study aims to determine and analyze the effect of Net Profit Margin (NPM), Debt to Equity Ratio (DER), Total Asset Turnover (TATO) on Profit Growth. The population in this study are consumer goods industry companies listed on the Indonesia Stock Exchange (IDX) for the 2018 – 2019 period. From the sampling technique in the form of purposive sampling, the number of companies is 30 companies. The data analysis technique of this research is multiple linear regression analysis which is processed using SPSS 21 software. The results show empirically that partially the Net Profit Margin (NPM) variable affects profit growth. Meanwhile, Debt to Equity Ratio (DER), Total Asset Turnover (TATO) has no partial effect on profit growth.